2017
DOI: 10.1016/j.funeco.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Algal polysaccharide utilisation by saprotrophic planktonic marine fungi

Abstract: The functional roles that marine mycoplankton fulfil are poorly understood, resulting in a lack of knowledge of their ecology. Here we show, using DNA Stable Isotope Probing with 13 C-labelled diatom polysaccharide microgels, that mycoplankton assimilate algal-derived particulate organic carbon (POC), identifying two genera, Malassezia and Cladosporium, which are active saprotrophs in coastal waters. We subsequently isolated polysaccharide-utilising Cladosporium strains from the same ecosystem and that are wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…In marine environments fungi appear to be more abundant in > 3 up to 90 µm size fractions (Gutiérrez, Pantoja, Tejos, & Quiñones, 2011; Richards et al., 2015), suggesting they themselves are large or are particle associated. It is likely that most saprotrophic fungi would be attached/associated with some form of particle, either organic (i.e., transparent exopolymer particles (Cunliffe et al., 2017)) or synthetic such as plastic, as this is where they can readily access carbon for growth. This means that without detailed size fractionation it would be difficult to separate true free‐living fungal communities in seawater.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In marine environments fungi appear to be more abundant in > 3 up to 90 µm size fractions (Gutiérrez, Pantoja, Tejos, & Quiñones, 2011; Richards et al., 2015), suggesting they themselves are large or are particle associated. It is likely that most saprotrophic fungi would be attached/associated with some form of particle, either organic (i.e., transparent exopolymer particles (Cunliffe et al., 2017)) or synthetic such as plastic, as this is where they can readily access carbon for growth. This means that without detailed size fractionation it would be difficult to separate true free‐living fungal communities in seawater.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of OTUs classified were saprotrophs. Saprotrophic fungi are key regulators of nutrient cycles in terrestrial systems and it is thought this is true in marine ecosystems (Amend et al., 2019; Cunliffe et al., 2017; Grossart et al., 2019). It has been suggested that early biofilm colonizers on plastics, such as Bacteria, can be attracted not to the plastic's surface, but to the biofilm that could increase their access to nutrients (Oberbeckmann & Labrenz, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some taxa of the early-diverging fungal phylum Chytridiomycota, mainly the members of Chytridiomycetes (chytrids) (50), are virulent parasites (57-62) that can attenuate phytoplankton productivity. In addition to parasitism, some studies have shown that marine fungi metabolize phytoplankton-derived organic matter (13,14,63). The importance of interactions in driving eukaryotic diversity has been suggested for the global ocean (64), as well as for fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic fungi, for example, may lead to disintegration of planktonic species with negative consequences for sinking fluxes 176 , while there is limited knowledge about the role of saprophytic aquatic fungi in processes such as transformation of carbon in lake or marine snow 177 . In marine systems, saprotrophic mycoplankton can utilize algal polysaccharides, indicating that aquatic fungi can affect the flow of OM in multiple, but poorly understood ways 178 .…”
Section: Fungi In Open Water (Lakes and Oceans)mentioning
confidence: 99%